Doktrin Roh Kudus dalam Kehidupan Umat Kristen - Ifris Aprilia; Nabylla Aprilia; Ferdick Kaswara; Sarmauli (INDO PUBLISHING, 2025)
This study aims to systematically reconstruct the doctrine of the Holy Spirit (Pneumatology) and analyze its relevance to the spiritual life of Christians, especially within the Indonesian context. As a qualitative study, this research employs a literature review design, utilizing content analysis and theological hermeneutics on primary data from the Bible and secondary data from systematic theology books and journal articles. The findings affirm that the Holy Spirit is an active and transformative divine person within the Trinity. His roles are comprehensive: as a Guide into all truth, a Comforter who provides strength, and a Sanctifier who produces the fruit of the Spirit to shape Christ-like character. Furthermore, the Holy Spirit empowers believers with spiritual gifts for effective ministry and witness. The study concludes that a sound understanding of Pneumatology is crucial for the church to navigate complex modern challenges, moving beyond mere doctrinal formalism to a dynamic and powerful faith experience. The implication of this research underscores the need for holistic theological education that integrates the balance between the gifts and the fruit of the Spirit in congregational development, fostering a transformative and applicable spirituality.